A Comparative Study Between the Antibacterial Effect of Alcoholic Extract and Hot Water Extract of Fresh Turmeric on Some Pathogenic Bacteria - Taher, Essam Mohammad (Medical Science Journal for Advance Research, 2025)
In a study evaluating antibiotic susceptibility, Staphylococcus aureus exhibited resistance to Penicillin and Clindamycin but was sensitive to Levofloxacin and Chloramphenicol. In contrast, Streptococcus pyogenes showed resistance to all four antibiotics. Pseudomonas aeruginosa demonstrated resistance to Amikacin, Levofloxacin, and Ceftazidime, while showing sensitivity to Meropenem and Imipenem, and resistance to Piperacillin/Tazobactam. Escherichia coli was highly sensitive to all antibiotics except Ceftazidime, which showed high resistance. Salmonella typhi exhibited resistance to Ceftazidime and Piperacillin/Tazobactam, intermediate sensitivity to Imipenem and Levofloxacin, and sensitivity to Meropenem and Amikacin. The study also assessed the inhibitory activity of turmeric extracts. The alcoholic extract of turmeric was highly effective against all tested bacteria compared to the hot water extract. At 200 µg/ml, both extracts inhibited all bacteria, with the least effect on Pseudomonas aeruginosa. At 150-100 µg/ml, both extracts inhibited all bacteria except Pseudomonas aeruginosa. At 50 µg/ml, the alcoholic extract showed no inhibitory activity against Pseudomonas aeruginosa and Staphylococcus aureus but inhibited other bacteria, while the hot water extract only inhibited Streptococcus pyogenes. These findings highlight the concentration-dependent antibacterial efficacy of turmeric extract